2021
DOI: 10.3390/ijms22083899
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease: Focus on New Biomarkers and Lifestyle Interventions

Abstract: Nonalcoholic fatty liver disease (NAFLD) is considered a hepatic manifestation of metabolic syndrome, characterized from pathological changes in lipid and carbohydrate metabolism. Its main characteristics are excessive lipid accumulation and oxidative stress, which create a lipotoxic environment in hepatocytes leading to liver injury. Recently, many studies have focused on the identification of the genetic and epigenetic modifications that also contribute to NAFLD pathogenesis and their prognostic implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 146 publications
0
24
0
Order By: Relevance
“…Kang R et al [ 35 ] described that lipid peroxidation in ferroptosis induces pyroptosis, suggesting a link between ferroptosis and other forms of cell death in sepsis. Lipid peroxidation is involved in several disease conditions [ 36 ] like cardiovascular disease [ 37 ] cancer [ 38 ], Alzheimer [ 39 ] and chronic diseases such as NAFLD [ 40 ], Multiple Sclerosis [ 41 ], COPD [ 42 ] and Diabetes mellitus [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kang R et al [ 35 ] described that lipid peroxidation in ferroptosis induces pyroptosis, suggesting a link between ferroptosis and other forms of cell death in sepsis. Lipid peroxidation is involved in several disease conditions [ 36 ] like cardiovascular disease [ 37 ] cancer [ 38 ], Alzheimer [ 39 ] and chronic diseases such as NAFLD [ 40 ], Multiple Sclerosis [ 41 ], COPD [ 42 ] and Diabetes mellitus [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although NASH CRN does not exactly define NASH by using the NASH score [ 24 ], we determined NASH according to the NASH score of ≥ 4 (with at least 1 point each in inflammation and ballooning) [ 25 ]. This threshold was based on the inclusion criteria of most of the Food and Drug Administration (FDA)-approved clinical trials to develop NAFLD therapeutic drugs [ 26 ]. Clinical characteristics of patients are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…NAFLD has been considered a complex disease, which is also frequently associated with other pathologies such as diabetes and cardiovascular and chronic kidney diseases [ 26 ]. Multiple studies have revealed that NAFLD is a hepatic manifestation of metabolic syndrome, characterised by pathological changes in carbohydrate and lipid metabolism [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes, which are well recognized active cell–cell communicators, are produced not only from parenchymal cells but also from non-parenchymal cells; it has been proven that they are able to deliver their bioactive cargo from cell of origin to recipient cells. In the literature, their relevant involvement in NAFLD disease progression and degeneration has been extensively documented, as they promote inflammation [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%